Developing and applying clinically useful approaches to identify individuals with familial hypercholesterolemia in the UK - Humphries, SE; Neil, H (2010)
Familial hypercholesterolemia (FH) meets internationally agreed criteria for screening, and systematic national screening programs should, therefore, be initiated. Cascade testing (to screen at-risk relatives) of known index cases with FH (using a combination of mutation information and lipid levels) is cost effective, and is an evidence?based method for the identification of undiagnosed cases, but calculations indicate that this approach will, at best, identify 40% of the predicted cases; therefore, additional strategies are needed. Modeling suggests that universal screening will not be cost effective; however, approaches such as identifying potentially affected individuals participating in national Vascular Health Check programs can complement cascade testing. Pilot studies to determine feasibility and practicality of FH patient identification by cholesterol-level screening in children, as well as by general practitioner electronic note searching, are also warranted. © 2010 Future Medicine Ltd.